Pesan Akhlak dalam Sinetron para Pencari Tuhan Jilid 15 (Analisis Semiotika Roland Barthes) - Daffaul Haqqi (Al-Balagh : Jurnal Komunikasi Islam, 2024)
This research aims to analyze the moral message in the soap opera "Para Pencari God Volume 15" using Roland Barthes' semiotic approach. This research is content analysis research using a qualitative approach. The researcher used C=coding, in this case the subjects and objects in this research are called the population, therefore the researcher then looked for scenes or scenes that contained moral messages in the soap opera. The researcher's data collection technique used documentation and observation. The results of this research provide an in-depth understanding of how soap operas such as "Para Pencari God Volume 15" can be an important vehicle for spreading moral and moral values to the wider community through the medium of mass media. In the conclusion, the soap opera "The God Seekers Volume 15" presents denotative messages that reflect various values and themes that are relevant to everyday life. Through interactions between characters, events that occur, and dialogues that occur, reflections on morality, conflict, responsibility, and relationships between humans. The connotative message in the soap opera "Para Pencari God Volume 15" is to present deeper layers of meaning for the audience. Through the use of emotional associations, nuances, the use of symbols, as well as context and culture, relevant moral, spiritual and social messages with everyday life. Then in this soap opera several elements of myth are depicted, including depictions of the power of prayer, myths about the importance of sincerity in spiritual relationships and myths about karma or punishment commensurate with actions.